Dose-rate constant and air-kerma strength evaluation of a new 125I brachytherapy source using Monte Carlo (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Brachytherapy is a modality of radiotherapy which treats tumors using ionizing radiation with sources located close to the tumor. The sources can be produced from several radionuclides in various formats, such as Iodine‑125 seeds and Iridium‑192 wires. In order to produce a new Iodine‑125 seed in IPEN/CNEN and ensure its quality, it is essential to describe the dosimetry of the seed, so when applied in a treatment the lowest possible dose to neighboring healthy tissues can be reached. The report by the AAPM’s Task Group 43 U1 is a document that indicates the dosimetry procedures in brachytherapy based on physical and geometrical parameters. In this study, dose-rate constant and air-kerma strength parameters were simulated using the Monte Carlo method radiation transport code MCNP4C. The air-kerma strength is obtained from an ideal modeled seed, since its actual value should be measured for seeds individually in a specialized lab with a Wide-Angle Free-Air Chamber (WAFAC). Dose-rate constant and air-kerma strength are parameters that depends on intrinsic characteristics of the source, i.e. geometry, radionuclide, encapsulation, and together they define the dose-rate to the reference point, defined as the dose-rate to a point 1 cm away from the geometric center of the source, in its transverse plane. This study presents the values found for these parameters with associated statistical uncertainty, and is part of a larger project that aims the full dosimetry of this new seed model, including experimental measures.